ANALISIS PERLAKUAN AKUNTANSI PENDAPATAN PADA PT. BANK MALUKU AMBON - Papilaya, Mia; Ilat, Ventje; Wokas, Heince (Universitas Sam Ratulangi, 2017)
The bank is a financial institution which main function is to collect funds from the public, distributing funds to the community, and also provides services in the form of banking service. Each company in the preparation of financial statements is an important basis for determining the financial performance of companies which includes interest income. This study was conducted to see how the accounting treatment of income at PT. Bank Maluku, whether it has been implemented in accordance with PSAK No.31. This type research usedÂ qualitative data method. Source data used are primary data. The method of analysis done is descriptive method. The results showed in the accounting treatment of interest income at PT. Bank Maluku. Interest income is income earned from the investment of bank funds in productive asset. Accrued interest income (accrual basis), except for interest income from troubled assets. It can be seen that the accounting treatment of income at PT. Bank Maluku is in compliance with PSAK No.31.Keywords : Treatment, Interest Income